Answer:
7x8 is 56 plus four plus one equals 61
Step-by-step explanation:
Answer:$40
Step-by-step explanation:
The average rate of change of f(x) over the interval -1 ≤ x ≤ 1 is -1.
Given the functionover the interval -1 ≤ x ≤ 1, we need to calculate the difference in the function values at the endpoints of the interval and divide it by the difference in the x-values.
The value of f(x) at the endpoint x = -1:
f(-1) = (-1)² - (-1) - 1 = 1 + 1 - 1 = 1
Now, the value of f(x) at the endpoint x = 1:
f(1) = (1)² - (1) - 1 = 1 - 1 - 1 = -1
The difference in the function values is:
f(1) - f(-1) = -1 - 1 = -2
The difference in the x-values is:
1 - (-1) = 2
Now, we can calculate the average rate of change:
Average rate of change = (f(1) - f(-1)) / (1 - (-1)) = -2 / 2 = -1
Therefore, the average rate of change of f(x) over the interval -1 ≤ x ≤ 1 is -1.
Learn more about average rate;
#SPJ12
Answer:
ff has an average rate of change of zero over the interval
−
1
≤
�
≤
2
−1≤x≤2minus, 1, is less than or equal to, x, is less than or equal to, 2.
Step-by-step explanation:
-1≤x≤2
B) proportion
C) integer
D) volume
Answer:
Answer is 4.2 - I just took the quiz
Step-by-step explanation: